2022
DOI: 10.1007/s11764-022-01178-z
|View full text |Cite
|
Sign up to set email alerts
|

Needs and preferences of breast cancer survivors regarding outcome-based shared decision-making about personalised post-treatment surveillance

Abstract: Purpose In this study, we explored how patients experience current information provision and decision-making about post-treatment surveillance after breast cancer. Furthermore, we assessed patients’ perspectives regarding less intensive surveillance in case of a low risk of recurrence. Methods We conducted semi-structured interviews with 22 women in the post-treatment surveillance trajectory in seven Dutch teaching hospitals. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…This can be supported by the use of prediction models, such as the INFLUENCE-nomogram [ 4 ]. Women indicate to welcome this type of information, to support the process of SDM about post-treatment surveillance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be supported by the use of prediction models, such as the INFLUENCE-nomogram [ 4 ]. Women indicate to welcome this type of information, to support the process of SDM about post-treatment surveillance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The INFLUENCE-nomogram is a prediction model which enables the estimation of individual risks for LRRs and SPs within the first 5 years after surgery based on patient-, tumour and treatment characteristics [ 4 ]. This model can be used to identify patients who might benefit from less or more intensive surveillance and to inform patients about their personal risks within the process of shared decision-making (SDM) about personalised surveillance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that shared decision-making about personalised surveillance is desirable [ 10 , 12 ]. General overestimations of the risk for LRR might hinder objective patient information which is required for shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The objective risk estimation can therefore be incorporated into a tool, such as a patient decision aid, to support the process of shared decision-making regarding surveillance. In the patient decision-aid, information on the aim and options for surveillance can be provided to put the risk information and need for personalised surveillance in context for the patient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Female breast cancer was the most commonly diagnosed cancer, with 2.3 million new cases (11.7%), surpassing lung cancer [1]. The survival rate in patients with breast cancer has improved due to early diagnosis and improved treatment [2,3]. Almost 88% of breast cancer patients survive for ve years or more [4].…”
Section: Introductionmentioning
confidence: 99%